GaN Power p–n Diodes on Hydride Vapor Epitaxy GaN Substrates with Near‐Unity Ideality Factor and <0.5 mΩ cm2 Specific On‐Resistance. Issue 4 (22nd January 2022) - Talesara, Vishank; Zhang, Yuxuan; Chen, Zhaoying; Zhao, Hongping; Lu, Wu
Abstract : Herein, vertical GaN p–n diodes grown by metal organic chemical vapor deposition on hydride vapor epitaxy bulk GaN substrates are reported. The devices exhibit an ideality factor of 1.15, a turn‐on voltage of 3.2 V at 100 A cm −2, over 1 kV breakdown voltage, and specific on‐state resistance of 0.47 mΩ cm 2, leading to a Baliga's figure of merit of ≈2.2 GW cm −2 . The low specific on‐resistance, low turn‐on voltage, and the near‐unity ideality factor demonstrated here are attributed to the high epitaxial material quality and optimized low anode contact resistance. Abstract : This work demonstrates a vertical GaN p–n power diode with an ideality factor of 1.15, turn‐on voltage of 3.2 V at 100 A cm −2, reverse leakage current density of 7.8 × 10 −6  A cm −2, over 1 kV breakdown voltage, and specific on‐state resistance of 0.47 mΩ cm 2 . This leads to a Baliga's figure of merit of ≈2.2 GW cm −2 .